Still this love goes on - Sainte-Marie, Buffy; Flett, Julie (Vancouver : Greystone Kids/Greystone Books, 2022)
This beautifully illustrated tribute to Indigenous communities everywhere brings to life an Academy Award-winning Cree icon's song of the same name, combining meaningful lyrics with breathtaking illustrations to create an extraordinary piece of art.
Kirkus Starred, August 2022
Booklist, September 2022
2.4
K-3
AD370L
Keywords: Indigenous peoples -- Juvenile fiction; Indigenous peoples -- Fiction; Stories in rhyme; Love -- Juvenile fiction; Cree Indians -- Juvenile fiction; Songs, English -- Canada